Playing on the edge : sadomasochism, risk, and intimacy - Newmahr, Staci (Indiana University Press, 2011)
Representations of consensual sadomasochism range from the dark, seedy undergrounds of crime thrillers to the fetishized pornographic images of sitcoms and erotica. In this pathbreaking book, ethnographer Staci Newmahr delves into the social space of a public, pansexual SM community to understand sadomasochism from the inside out. Based on four years of in-depth and immersive participant observation, she juxtaposes her experiences in the field with the life stories of community members, providing a richly.